DESIGNING AN ETHNOGRAPHIC APPROACH TO AUTHENTIC LEADERSHIP AND ITS RELATIONSHIP WITH THE FIVE T RITUALS AND DYNAMIC CAPABILITIES: AN APPLIED EXPLORATORY STUDY IN AL-FURAT CHEMICALS MANUFACTURING COMPANY IN BABYLON - Marwa Hassan Al-Shammari; Zada Muhammad Ali; Sadiq Anwar (Scholars Digest Publishing, 2024)
This study aims to demonstrate the extent to which the members of the study sample are aware of the importance of authentic leadership in applying the elements of the Five Cs and benefiting from the dynamic capabilities that characterize them in order to develop the company under study. The researcher reached a set of conclusions, and the most important of which are: The opinions of the leaders of Al-Furat Company match their behaviors, in addition to their understanding of the activities and their encouragement of their employees and telling them the truth about some things despite their difficulty. The need for the company’s leaders is to enhance the behavior of the informing subordinates of all the difficult facts at work and giving them the appropriate opportunity to defend their core values and adequately listen to their opinions, in addition to taking the note of feedback before making decisions. The lower the level of these behaviors will disturb the relationship between leaders and subordinates as well as create confusion in the psychological environment of the company.
Keywords: Ethnographic approach, Authentic leadership, Subordinates, Rituals and dynamic capabilities, Exploratory study, Al-Furat General Company.; Z